PANDANGAN MAHASISWA CALON GURU DALAM PENGGUNAAN MODEL GAMIFIKASI DALAM PEMBELAJARAN MATEMATIKA - Muhammad Ghiyats Ristiana; Jarnawi Afgani Dahlan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Games already become the fun thing that everybody should try. Therefore, learning with some elements of games can be applied to engage student. Even more in mathematics learning which tend difficult to undertand if they don’t like mathematics. The aim of this study are to see prospective teachers’ responses about games and gamification according to their view. This study use descriptive qualitative study and literature review to get the answer. In order to do so, we provide questionnaire in the form of google form for 183 prospective teachers. We analyzed that questionnaire descriptively. The results is more than 60% prospective teachers like game, and more than 90% prospective teachers interested in following mathematics learning with gamification model. Based on results, we conclude that someone who like game is because they can have fun, to get rid of bored, to improve their thinking ability, social interaction, solve the challenges, get a new knowledge, competition, and realize what they can’t realize in real life. Whereas someon who don’t like game is because they will wasting their time, quickly saturated because the repetitive mission or challenges, don’t like challenges, afraid of addiction and not interested with some games.